Space charge characteristics and dielectric properties of PANI/PP‐g‐MAH/PP ternary composite - Guochang Li; Tianzhen Liu; Zhenlu Gu; Xiaolong Chen; Beibei Sun; Yuanwei Zhu; Shengtao Li; Yanhui Wei (High Voltage)
Abstract Space charge accumulation in polypropylene materials for direct current capacitor will accelerate the ageing of the materials, resulting in the degradation of their insulation properties. Besides, it will also affect the dielectric properties of the capacitor in a long term. In this paper, a ternary composite of polyaniline (PANI)/maleic anhydride functionalised PP (PP‐g‐MAH)/polypropylene (PP) based on the PANI@ dopamine (PDA) coating structure is constructed from two perspectives of PP matrix grafting and PANI nano particle. This method takes advantage of the high permittivity and good compatibility of PANI to improve the relative dielectric constant of the composite while introducing deep traps inside the composite to inhibit space charge accumulation coating. The experimental results show that with the increase in PANI content, the maximum relative permittivity can be increased by 62%. The addition of the appropriate amount of PANI can effectively inhibit the space charge accumulation. The relative dielectric constant of the composite decreases significantly due to the heteropolar space charge. The relative dielectric constant of the modified polyaniline composites decreased significantly. The reduction rate decreased from 38% before modification to 12% after modification. This work has certain guiding significance for solving space charge problem of direct current capacitor.